2016
DOI: 10.1021/acs.jpcb.5b08579
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Dynamics Study of Tributyl Phosphate and Diamyl Amyl Phosphonate Self-Aggregation in Dodecane and Octane

Abstract: A molecular dynamics model for tributyl phosphate (TBP) and diamyl amyl phosphonate (DAAP) is presented using the Generalized AMBER Force Field (GAFF) and the AM1-BCC method for calculated atomic charges with a modification to the phosphorus-containing dihedral parameters. The density and average molecular dipole in a neat liquid simulation, and dimerization in dodecane and octane diluents, compare favorably to experimental values. At low extractant concentration, investigation of the dimer structure reveals t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
1
13
1
Order By: Relevance
“…These results are in good agreement with the experimental results published by Motokawa et al . Previous MD simulations reported in the literature describe either TBP dimers in alkane‐diluted organic phases,,, or TBP trimers or even tetramers in more concentrated solutions . However, all of these MD simulations were performed for “dry” organic phases (i.e., without any water molecules), although TBP is known to be very hydrophilic.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…These results are in good agreement with the experimental results published by Motokawa et al . Previous MD simulations reported in the literature describe either TBP dimers in alkane‐diluted organic phases,,, or TBP trimers or even tetramers in more concentrated solutions . However, all of these MD simulations were performed for “dry” organic phases (i.e., without any water molecules), although TBP is known to be very hydrophilic.…”
Section: Resultssupporting
confidence: 90%
“…The absence of water molecules that appear to play a significant role in the structuring of these organic phases makes the relationship between experimental results and these MD simulations very difficult to establish because, by definition, TBP aggregates including water molecules are not taken into account, which implies a biased count of TBP aggregates. Herein, similar to recent simulations reported by the groups of Servis or Ivanov, the actual experimental compositions of the organic phases were taken into account in the MD simulations, which allowed the experimental data to be reproduced and the aggregation of TBP and the corresponding molecular structures to be described in agreement with the experimental results.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…TBP being smaller in comparison to D2EHPA, the intensity of van der Waals force of attraction in TBP is less than that of D2EHPA. Thus, viscosity of TBP is less than that of D2EHPA though both can form dimers through the phosphoryl oxygen atom 8,54 . As the concentration of TBP and D2EHPA increases in mixtures B and D, respectively, the length of carbon chain increases, which weakens the dipole–dipole interactions between the phosphoryl group.…”
Section: Resultsmentioning
confidence: 99%
“…22,28,31 In this work the surfactant tri-n-butyl phosphate (TBP) is chosen because of its ubiquity in solvent extraction applications, 1,32 notably in the Plutonium Uranium Reduction EXtraction (PUREX) process, and because it has been the topic of extensive study in the MD modeling literature. 8,10,20,[33][34][35][36][37][38][39][40][41][42] Prior work 7,20,42,43 has shown that TBP adsorbs to the water/organic interface with its dipole orthogonal and alkyl tails parallel to the interface plane. While the extraction of water from the interface by TBP has been qualitatively described in the literature, 7,42 it remains to be understood -either qualitatively or quantitatively -how TBP adsorption influences the capillary wave front, including its heterogeneity, fluctuations in space, and the resulting mechanisms for water extraction into the organic phase.…”
Section: Introductionmentioning
confidence: 99%